Respuesta :

[tex]\huge\textbf{Hey there!}[/tex]

[tex]\huge\textsf{-1 - [-z]}\\\\\huge\textsf{= -1 - [- -2]}\\\\\huge\textsf{= -1 - - 2}\\\\\huge\textsf{= -1 + (-2)}\\\\\huge\textsf{= -1 - 2}\\\\\huge\textsf{= -3}\\\\\\\huge\textbf{Therefore, your answer is: \boxed{\mathsf{-3}}}\huge\checkmark[/tex]

[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]

Answer:

-3

Step-by-step explanation:

Evaluate - 1 - ( - z ) where z = -2

you can find this out because when there are two minuses by each other it equals a positive but then z = -2 so that adds another minus so it narrows it down to -1+-2 which equals 3